Review of Tau, R., Kloetzer, L., & Henein, S. (2024). Barefoot academic teaching: Performing arts as a pedagogical tool in higher education (Edition Scenario Vol. VII). Schibri. - Eva Göksel (SCENARIO: Journal for Performative Teaching, Learning, Research)
In the true spirit of improvisation, this book is an across the board “yes”! It places embodied teaching and learning at the centre of the university curriculum and as such,it should appeal to readers with a strong interest in the role of the arts in academia: students, researchers, administrators, performers, and teachers/lecturers alike, because it thoughtfully encompasses voices from almost each of these groups.